An artificial photosynthetic system for photoaccumulation of two electrons on a fused dipyridophenazine (dppz)–pyridoquinolinone ligand. Issue 17 (12th April 2018) - Lefebvre, Jean-François; Schindler, Julian; Traber, Philipp; Zhang, Ying; Kupfer, Stephan; Gräfe, Stefanie; Baussanne, Isabelle; Demeunynck, Martine; Mouesca, Jean-Marie; Gambarelli, Serge; Artero, Vincent; Dietzek, Benjamin; et al.
Abstract : The π-extended ligand of a ruthenium complex stores two photo-generated electrons, mimicking a key step in photosynthesis. Abstract : Increasing the efficiency of molecular artificial photosynthetic systems is mandatory for the construction of functional devices for solar fuel production. Decoupling the light-induced charge separation steps from the catalytic process is a promising strategy, which can be achieved thanks to the introduction of suitable electron relay units performing charge accumulation. We report here on a novel ruthenium tris-diimine complex able to temporarily store two electrons on a fused dipyridophenazine–pyridoquinolinone π-extended ligand upon visible-light irradiation in the presence of a sacrificial electron donor. Full characterization of this compound and of its singly and doubly reduced derivatives thanks to resonance Raman, EPR and (TD)DFT studies allowed us to localize the two electron-storage sites and to relate charge photoaccumulation with proton-coupled electron transfer processes.